NMDA Receptors in GABAergic Synapses during Postnatal Development - Cserép, Csaba (Public Library of Science, 2012)
GABA (gamma-aminobutyric-acid), the main inhibitory neurotransmitter in the adult brain, exerts depolarizing (excitatory) actions during development and this GABAergic depolarization cooperates with NMDARs (N-methyl-D-aspartate receptors) to drive spontaneous synchronous activity (SSA) that is fundamentally important for developing neuronal networks. Although GABAergic depolarization is known to assist in the activation of NMDARs during development, the subcellular localization of NMDARs relative to GABAergic synapses is still unknown. Here, we investigated the subcellular distribution of NMDARs in association with GABAergic synapses at the developmental stage when SSA is most prominent in mice. Using multiple immunofluorescent labeling and confocal laser-scanning microscopy in the developing mouse hippocampus, we found that NMDARs were associated with both glutamatergic and GABAergic synapses at postnatal day 6–7 and we observed a direct colocalization of GABA(A)- and NMDA-receptor labeling in GABAergic synapses. Electron microscopy of pre-embedding immunogold-immunoperoxidase reactions confirmed that GluN1, GluN2A and GluN2B NMDAR subunits were all expressed in glutamatergic and GABAergic synapses postsynaptically. Finally, quantitative post-embedding immunogold labeling revealed that the density of NMDARs was 3 times higher in glutamatergic than in GABAergic synapses. Since GABAergic synapses were larger, there was little difference in the total number of NMDA receptors in the two types of synapses. In addition, receptor density in synapses was substantially higher than extrasynaptically. These data can provide the neuroanatomical basis of a new interpretation of previous physiological data regarding the GABA(A)R-NMDAR cooperation during early development. We suggest that during SSA, synaptic GABA(A)R-mediated depolarization assists NMDAR activation right inside GABAergic synapses and this effective spatial cooperation of receptors and local change of membrane potential will reach developing glutamatergic synapses with a higher probability and efficiency even further away on the dendrites. This additional level of cooperation that operates within the depolarizing GABAergic synapse, may also allow its own modification triggered by Ca(2+)-influx through the NMDA receptors.